Improving the level of physical development and functional preparedness athletes in sports dancing on the stage of specialized basic training means step aerobics - Galyna Artemyeva; Elena Avramenko; Sergey Gumenyuk (Kharkiv State Academy of Physical Culture, 2016)
Purpose: make analyze the impact of the step aerobics on the indicators of physical development and functional preparedness of athletes in Dance Sport on the stage of specialized basic training. Material & Methods: 20 athletes (10 sport duets) aged 14-15 years were divided into two groups: control (CG) and experimental (EG). To achieve the objectives we used methods: theoretical - analysis and synthesis data of scientific and methodological literature; pedagogical methods: pedagogical observation; pedagogical testing; medical and biological methods: anthropometry, functional methods of research; methods of mathematical statistics. Results: after the implementation of a training process means step aerobics significantly improved indicators of cardio-respiratory system of athletes in Dance Sport. Conclusions: materials research to assess allow us to estimate the extent of influence of step aerobics on indicators of physical development and functional preparedness athletes in Dance Sport on the stage of specialized basic training.